ТЕРМОДИНАМІЧНІ ВЛАСТИВОСТІ СРІБЛОВМІСНИХ СПОЛУК СИСТЕМИ Ag–Fe–Sn–S, ОТРИМАНИХ НИЗЬКОТЕМПЕРАТУРНИМ ТВЕРДОФАЗНИМ СИНТЕЗОМ - Moroz , Mykola; Reshetnyak, Oleksandr; Demchenko, Pavlo; Prokhorenko , Myroslava; Soliak, Lyudmyla; Rudyk , Bohdan; Pereviznyk , Orest; Prokhorenko , Serhii (V.I.Vernadsky Institute of General and Inorganic Chemistry, 2020)
The existence of the AgFeS2 and Ag2FeS2 compounds in the equilibrium concentration space of the Ag–Fe–S system was established by the EMF method. Investigations were performed in the electrochemical cells (ECCs) of the type (−) С | Ag | SЕ | R(Ag+) | PЕ | С (+), where C is the inert electrode (graphite), Ag is the negative (left) electrode, SE is the solid electrolyte, PE is the positive (right) electrode, R(Ag+) is the region of Ag+ diffusion into PE. Ag2GeS3 glass was used as the solid-state electrolyte with purely Ag+ ionic conductivity. The SnS2–FeS2–Ag2FeS2 (A) phase region of the Ag–Fe–Sn–S system is formed with the participation of three-component compounds. The cross-sections AgFeS2–Ag2FeSnS4, AgFeS2–Ag2FeSn3S8, and AgFeS2–SnS2 carry out the division of (A). Spatial position of the two-phases FeS2–AgFeS2, AgFeS2–Ag2FeS2 and three-phases AgFeS2–Ag2FeSn3S8–SnS2, AgFeS2–Ag2FeSnS4–Ag2FeSn3S8 regions of (A) regarding the point of silver was used to write the equations of the overall potential-forming reactions. Reactions were realized in the positive electrodes of ECCs. PE at the stage of the cell preparation is a well-mixed composition of finely ground (particle size ~5 μm) of the compounds Ag2S, FeS, FeS2 and Ag2S, FeS, FeS2, SnS2 in two- and three-phases regions of (A), respectively. The ratios of compounds in PE of ECCs were determined from the equations of the overall potential-forming reactions in respective phase regions. The decomposition of the metastable set of binary compounds and the synthesis of the equilibrium set of phases were carried out in the nanoscale region of the PE of ECC in contact with SE, i.e. in the R(Ag+) region. The Ag+ ions displaced from the left electrode to the right one for thermodynamic reasons act as nucleation centers for the equilibrium compounds. The process of forming the equilibrium set of phases in the R(Ag+) region for the particle size of the metastable phase mixture ~5 μm and Т=580 K took less than 72 h. The linear dependencies of EMF vs T of ECCs with PE of two- and three-phases regions were established in the ranges of (455–519) K and (450–514) K, respectively. Based on these dependencies, the standard thermodynamic quantities of the AgFeS2, Ag2FeS2, Ag2FeSnS4, and Ag2FeSn3S8 compounds were experimentally determined for the first time. The reliability of the established equilibrium sets of phases that provide the potential-forming reactions in ECCs was confirmed by the coincidence of the calculated and literature values of the Gibbs energy of the Ag2FeSnS4 and Ag2FeSn3S8 compounds.